Monitoring Sistem Transmisi Dan Distribusi Pada Pemancar Radio Fm Di Radio Republik Indonesia - Khaila Mardina Fauziah Awalia; Desmira Desmira (Jupiter: Publikasi Ilmu Keteknikan Industri, Teknik Elektro dan Informatika, 2024)
ticular building requires a lot of time. This monitoring is carried out continuously so that it is hoped that there will be an increase in efficiency, time, energy and costs in the electric power monitoring process. Each radio has an operational transmitter located in the broadcast studio so that the broadcast range is wider and clearer and can be enjoyed by the public. The research has several objectives, namely; [1] know about radio trans- mission, [2] know how audio distribution works, [3] how wave propagation works.